Is the real sector structure the determining factor of the financial sector structure of Iran's economy? - Seyedrohollah Ahmadi Hajiabadi (اقتصاد باثبات)
New viewpoints related to the financial system indicate that the financial structure of the economy is endogenously determined by the structure of the real sector; In this way, the structure of the real sector in each stage of economic development is considered an effective factor in the composition of the banking system and the capital market. Due to the lack of a similar internal study, statistical data for Iran's economy in the period of 1357-1399 was collected and in the first step, using the Gregory-Hansen cointegration test, the hypothesis of the existence of a long-term relationship between the real structure, the financial structure and other control variables have been investigated. The obtained result indicates the existence of a long-term relationship; The result was also confirmed by the ARDL bounds test approach. In the second step, the long-term and short-term model coefficients were estimated and then using causality test, the causal relationship between the structure of the financial and real sectors was investigated. The findings of the second phase show that the structure of the real sector of Iran's economy, which is measured by the ratio of the value added of the agricultural and industrial sectors to the total economy value added, has not had a significant effect on the financial structure of the economy although both short-run and long-run causality relationship verified. Considering the various types of financial services that the banking system and the capital market provide and the types of financial needs that companies need in the real sector, it can be concluded that the financial sector of Iran's economy has not been able to meet the financial needs of companies. In other words, the structure of Iran's financial sector is far from its desired level.